2018
DOI: 10.1002/tcr.201800049
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Hydrogels and Bionanocomposites Formed through the Mineralization and Regulated Charging

Abstract: The account presents survey of our systematic studies on chitosan. Only this polysaccharide bears cationic charges, possesses antimicrobial activity and wound healing ability that make it highly appropriate for using in medicine, biomedical engineering, cosmetics, food, packaging. However, its application meets with severe limitation. Chitosan belongs to polysaccharides that do not jellify solutions. Main approaches are based on the chemical modifications and cross-linking, but these treatments impairs therewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 113 publications
(191 reference statements)
0
13
0
Order By: Relevance
“…Preparation of homogeneous hydrogels by direct mixing of the solutions of oppositely-charged DNA and CS is not practically possible because of phase separation of poorly defined complexes. 17,31,37,40 (Supporting Information, Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of homogeneous hydrogels by direct mixing of the solutions of oppositely-charged DNA and CS is not practically possible because of phase separation of poorly defined complexes. 17,31,37,40 (Supporting Information, Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, potential applications of such systems are limited by inadequate mechanical properties of DNA hydrogels, strong dependence of their swelling on solution conditions, and vulnerability to enzymes. Some of aforementioned disadvantages can be significantly minimized by adapting a new approach suggested recently, to prepare a novel type of DNA-containing hydrogels based solely on physical (electrostatic) interactions between oppositely charged groups of chitosan and DNA. Chitosan, which is the only abundant cationic biomass-derived polysaccharide, covers a broad scope of applications including biomedicine and biomedical engineering, pharmaceutics, , cosmetics, food, , agriculture, environmental remediation, , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among the industrially relevant natural polysaccharides, chitosan is the only high molecular weight cationic biopolyelectrolyte; the other naturally occurring polysaccharides for industrial uses are either neutral or anionic [ 28 , 29 ].…”
Section: Naturally Occurring Polyelectrolytesmentioning
confidence: 99%
“…Postnova et al studied approaches in which monolithic hydrogels were prepared through mineralization of polysaccharide by a method of green sol-gel chemistry, compared with a method through the formation of polyelectrolyte complex [ 153 ]. It was found that both approaches were available for the preparation of films with nanoparticles and chitosan bionanocomposites.…”
Section: Organic Biopolymer-based Nanomaterials Applied In Food Pamentioning
confidence: 99%